2022
DOI: 10.7554/elife.74153
|View full text |Cite
|
Sign up to set email alerts
|

Absolute quantitation of individual SARS-CoV-2 RNA molecules provides a new paradigm for infection dynamics and variant differences

Abstract: Despite an unprecedented global research effort on SARS-CoV-2, early replication events remain poorly understood. Given the clinical importance of emergent viral variants with increased transmission, there is an urgent need to understand the early stages of viral replication and transcription. We used single-molecule fluorescence in situ hybridisation (smFISH) to quantify positive sense RNA genomes with 95% detection efficiency, while simultaneously visualising negative sense genomes, subgenomic RNAs, and vira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 94 publications
4
49
0
Order By: Relevance
“…Nevertheless, low levels of viral RNA genome equivalents remained detectable in the culture supernatant until the end of the experiment for both SARS‐CoV and SARS‐CoV‐2 (up to 192 h postexposure; Fig 1C ). Viral RNA was abundant also in supernatants from Remdesivir‐treated cultures and cultures exposed to heat‐inactivated SARS‐CoV‐2 until 192 h postexposure, arguing for high stability of the residual viral RNA of the inoculum, and against a constant replenishment of extracellular viral RNA pools as a reason for the stable RNA quantities (Fig 1D ), in line with reported longevity of the incoming genomic viral RNA (Lee et al , 2022 ). Notably, blunting signaling by type I interferons (IFNs) through the constant presence of the JAK/STAT inhibitor Ruxolitinib failed to enable secretion of infectious particles and viral RNA in the supernatant, suggesting that JAK/STAT‐dependent cell‐intrinsic innate immunity is not the underlying reason for the absence of detectable virus production (Fig 1A and C ).…”
Section: Resultssupporting
confidence: 80%
“…Nevertheless, low levels of viral RNA genome equivalents remained detectable in the culture supernatant until the end of the experiment for both SARS‐CoV and SARS‐CoV‐2 (up to 192 h postexposure; Fig 1C ). Viral RNA was abundant also in supernatants from Remdesivir‐treated cultures and cultures exposed to heat‐inactivated SARS‐CoV‐2 until 192 h postexposure, arguing for high stability of the residual viral RNA of the inoculum, and against a constant replenishment of extracellular viral RNA pools as a reason for the stable RNA quantities (Fig 1D ), in line with reported longevity of the incoming genomic viral RNA (Lee et al , 2022 ). Notably, blunting signaling by type I interferons (IFNs) through the constant presence of the JAK/STAT inhibitor Ruxolitinib failed to enable secretion of infectious particles and viral RNA in the supernatant, suggesting that JAK/STAT‐dependent cell‐intrinsic innate immunity is not the underlying reason for the absence of detectable virus production (Fig 1A and C ).…”
Section: Resultssupporting
confidence: 80%
“…Viral RNA was abundant also in supernatants from Remdesivir-treated cultures and cultures exposed to heat-inactivated SARS-CoV-2 until 192 hours post-exposure, arguing for a high stability of the residual viral RNA of the inoculum and against a constant replenishment of extracellular viral RNA pools as a reason for the stable RNA quantities ( Fig. 1D ), in line with reported longevity of the incoming genomic viral RNA (Lee et al 2022). Notably, blunting signaling by type I interferons (IFNs) through constant presence of the JAK/STAT inhibitor Ruxolitinib failed to enable secretion of infectious particles and viral RNA in the supernatant, suggesting that JAK/STAT-dependent cell-intrinsic innate immunity is not the underlying reason for the absence of detectable virus production ( Fig.…”
Section: Resultssupporting
confidence: 71%
“…Non-permeabilized monkey Vero E6 and human Calu-3 cells were analyzed by flow cytometry in order to check the binding activity of the 5D11B9 anti-IFITM2 mAb and verify the type III TM topology of IFITM2 on the plasma membrane. Vero E6 and Calu-3 cells have been widely used as cellular models for SARS-CoV-2 in in vitro studies due to their susceptibility to the virus and the endogenous expression of the proteins ACE2 and TMPRSS2 on the plasma membrane (Lee et al, 2022) (Shang et al, 2020). The cytofluorimetric analysis showed that the 5D11B9 anti-IFITM2 mAb was able to bind the cell surface of both cell lines in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%